Re-gendering Climate Change: Men and Masculinity in Climate Research, Policy, and Practice - Nagel, Joane; Lies, Trevor Scott (Frontiers in Climate, 2022)
In this Perspective, we argue that much climate change research conflates “gender” with “women.” We ask, what are the consequences of this conflation, and what do we learn when we follow sociologist George Homan’s (1964) classical command to “bring men back in” to our analysis of the gendered dimensions of climate change? We find, first, that scholarship on gender and climate change tends to depict women mainly as victims of the uneven impacts of climate change. While this assessment is accurate on its face, it leads to solutions that address the problem (women’s troubles), not its causes (men’s greater responsibilities and failures relating to climate change). We note that researchers’ focus on women’s suffering diverts attention from a thorough examination of the mechanisms and consequences of men’s domination of climate change research and policy. We find, further, that analysts’ gender/women conflation hinders redress of women’s injuries by camouflaging men’s blameworthiness and offering solutions that often increase women’s duties. Gender researchers’ emphasis on women’s plight and inequality obscures the exception that proves the rule: men wield the (sometimes) invisible hands that create and perpetuate the climate crisis at the expense of everyone, including women. In this Perspective, we acknowledge women’s relative vulnerability to climate change, outline in some detail the role of men and masculinity in the climate crisis, and identify the unique strengths that women and men each bring to the table to address the environmental challenges facing humanity.